Gentiopicroside modulates glucose homeostasis in high-fat-diet and streptozotocin-induced type 2 diabetic mice - Wang, Xing; Long, Dongmei; Hu, Xianghong; Guo, Nan (Frontiers in Pharmacology, 2023)
Gluconeogenesis is closely related to the occurrence and development of type 2 diabetes mellitus (T2DM). Gentiopicroside (GPS) is the main active secoiridoid glycoside in Gentiana manshurica Kitagawa, which can improve chronic complications associated with diabetes and regulate glucose metabolism. However, the effects and potential mechanisms by which GPS affects T2DM understudied and poorly understood. In this study, we systematically explored the pharmacological effects of GPS on T2DM induced by a high-fat diet (HFD) and streptozotocin (STZ) as well as explored its related mechanisms. The results showed that GPS supplementation discernibly decreased blood glucose levels, food intake and water consumption, ameliorated glucose intolerance, abnormal pyruvate tolerance, insulin resistance and dyslipidemia. Furthermore, GPS discernibly ameliorated pathological morphological abnormalities of the liver and pancreas, reduced hepatic steatosis and maintain the balance between α-cells and β-cells in pancreas. Moreover, GPS significantly inhibited gluconeogenesis, as evidenced by the suppressed protein expression of phosphoenolpyruvate carboxykinase (PEPCK) and glucose 6-phosphatase (G6Pase) in the liver. Additionally, the results of Western blot analysis revealed that GPS increased p-PI3K, p-AKT, and p-FOXO1 expression levels, and decreased FOXO1 expression at protein level in the liver. Furthermore, the results of the immunostaining and Western blot analysis demonstrated that GPS supplementation increased the expression of zonula occludens-1 (ZO-1) and occludin in the ileum. Collectively, these results indicate that GPS may inhibit hepatic gluconeogenesis by regulating the PI3K/AKT/FOXO1 signaling pathway and maintain intestinal barrier integrity, and ultimately improve T2DM. Together, these findings indicate that GPS is a potential candidate drug for the prevention and treatment of T2DM, and the results of our study will provide experimental basis for further exploration of the possibility of GPS as a therapeutic agent for T2DM.